Method of Recognition and Assistance Combining Passive RFID and Electrical Load Analysis That Handles Cognitive Errors. (26th October 2015) - Fortin-Simard, Dany; Bilodeau, Jean-Sébastien; Gaboury, Sébastien; Bouchard, Bruno; Bouzouane, Abdenour
The integration of wireless sensor technologies has increased awareness of many laboratories on the field of embedded network system. Many researchers seek exploiting these advances to develop technological assistance for frail people in smart homes. However, to reach the full potential of applications using network embedded systems such as assistive smart home, the first challenge to overcome is the recognition of the ongoing inhabitant activity of daily living (ADL). Moreover, to provide adequate assistance, it is essential to be able to detect every perceptive error. Such an approach proposes the use of ubiquitous sensors hidden in the environment for monitoring and detecting behavioral abnormalities associated with cognitive deficits and then does a proper guidance by providing advice using different kinds of effectors (screen, light, sound, etc.). In this paper, we present an affordable system that exploits a combination of passive RFID and the load signatures of appliances to assist elders and to detect errors related to cognitive impairment. The entire multi-sensor system has been implemented and deployed in a real prototype smart home. We present the promising results of our experiment on real daily routines.